Modulatory effects of ghrelin on sperm quality alterations induced by a fructose-enriched diet - Ramirez, Nicolás David (2019)
The objectives of this study were: 1) to evaluate the effects of a fructose enriched diet (FED) on rat3 sperm quality, epididymal function (i.e. oxidative stress and alpha-glucosidase expression) and4 testosterone concentrations; 2) to determine if the administration of ghrelin (Ghrl), reverses the5 effects induced by FED.6 After validating the protocol as an inductor of metabolic syndrome like-symptoms, adult male rats7 were assigned to one of the following treatments for 8 weeks: FED=10% fructose enriched in water8 (v/v); FED+Ghrl=fructose enriched diet plus Ghrl (6 nmol/animal/day, s.c.) from week 6 to 8; or9 C=water without fructose (n=5-10 animals/group).10 FED significantly decreased sperm concentration and motile sperm count/ml vs C (FED:19.0±1.6x106sperm/ml and 834.6±137.0, respectively vs C: 25.8±2.8x10611 and 1300.4±202.4,respectively; p<0.05); ghrelin injection reversed this negative effect (23.5±1.6x10612 sperm/ml and13 1381.7±71.3 respectively). FED resulted in hypogonadism, but Ghrl could not normalize testosterone14 concentrations (C: 1.4±0.1 ng/ml vs FED: 0.8±0.2 ng/ml and FED+Ghrl: 0.6±0.2 ng/ml ;p<0.05).15 Ghrelin did not reverse metabolic abnormalities secondary to FED. FED did not alter epididymal16 expression of antioxidants enzymes (superoxido-dismutase, catalase and glutathione peroxidases ?17 Gpx-). Nevertheless, FED+Ghrl significantly increased the expression of Gpx3 (FED+Ghrl:18 3.47±0.48 vs FED: 0.69±0.28 and C: 1.00±0.14; p<0.05). The expression of neutral alpha19 glucosidase, which is a marker of epididymal function, did not differ between treatments.20 In conclusion, the administration of Ghrl modulated the negative effects of FED on sperm quality,21 possibly by an epididymal increase in Gpx3 expression. However, Ghrl could not neither normalize22 the metabolism of FED animals, nor reverse hypogonadism.